2020
DOI: 10.1097/dad.0000000000001860
|View full text |Cite
|
Sign up to set email alerts
|

Image Morphometric Analysis of B Cells and Plasma Cells in Erythema Nodosum Leprosum With Clinicopathological Correlation

Abstract: Erythema nodosum leprosum (ENL) occurs as an immunological complication of multibacillary leprosy (MBL). The pathogenesis of ENL is long considered to be a T-cell-mediated process. The role of B cells and plasma cells in ENL is not well described in the literature. Therefore, we investigated the B-cell and plasma cell infiltrates in the skin biopsies of biopsy-proven cases of ENL by immunohistochemistry and image morphometry and compared the result with paucibacillary leprosy and MBL. Moreover, we sought a cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Here, we observed that there were no significant differences between patients and uninfected subjects in both transitional and plasmablast B cells, but a higher frequency of mature B cells was observed in both groups of patients with MB and ENL. We acknowledge that one limitation of the present study is the absence of functional analysis but a previous morphometric analysis of B cells and plasma cells in ENL demonstrated a positive correlation with CD3-positive pan T cells in the biopsy and a negative correlation with T regulatory -T cell ratio (32). In addition, CD27+CD21+ resting memory B cells were diminished in patients with MB leprosy, with only a slight significant increase in atypical memory B cells.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Here, we observed that there were no significant differences between patients and uninfected subjects in both transitional and plasmablast B cells, but a higher frequency of mature B cells was observed in both groups of patients with MB and ENL. We acknowledge that one limitation of the present study is the absence of functional analysis but a previous morphometric analysis of B cells and plasma cells in ENL demonstrated a positive correlation with CD3-positive pan T cells in the biopsy and a negative correlation with T regulatory -T cell ratio (32). In addition, CD27+CD21+ resting memory B cells were diminished in patients with MB leprosy, with only a slight significant increase in atypical memory B cells.…”
Section: Discussionmentioning
confidence: 62%
“…We acknowledge that one limitation of the present study is the absence of functional analysis but a previous morphometric analysis of B cells and plasma cells in ENL demonstrated a positive correlation with CD3-positive pan T cells in the biopsy and a negative correlation with T regulatory – T cell ratio ( 32 ).…”
Section: Discussionmentioning
confidence: 84%
“…In our earlier study involving the same cohort of patients, we could document a correlation of the dermal eosinophils with the dermal plasma cells in ENL. 7 We believe that the FoxP3:CD3 ratio is possibly related to the Th2 limb of the acquired immunity, both being characterized by their immunoregulatory functions. Thus, the Th2 limb recruits the eosinophils by the release of IL-4, 5, and 13.…”
Section: Discussionmentioning
confidence: 96%
“…The study population was similar to our previous published study. 7 The methodology is essentially similar to our previous study. 7 Routine hematoxylin and eosin stain was performed in all cases for the diagnosis, detailed histopathological assessment, and subtyping of all cases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation